2016
DOI: 10.1159/000447363
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Associated to Skipping Breakfast in Brazilian Health Service Patients

Abstract: Recent studies show that skipping breakfast is associated with an increased risk of obesity, diabetes and cardiovascular diseases. In this context, this study evaluated 400 patients from the Brazilian health service who had their nutritional status defined based on the body mass index and were classified as physically active or insufficient active. The energy intake and macronutrients was also assessed by a 24-hour dietary recall where the association of overweight/obesity with the investigated variables was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…In the present study, skipping breakfast was not correlated to overweight or obesity ( p = 0.631), thereby corroborating Betts et al [70], who did not find a difference between the body mass of breakfast eaters and skippers. Studies showed that skipping breakfast was correlated to obesity [71,72,73]. However, the population studied was different from ours, as our study evaluated the low-income Brazilian population using the CRs as the main source of food at lunch.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, skipping breakfast was not correlated to overweight or obesity ( p = 0.631), thereby corroborating Betts et al [70], who did not find a difference between the body mass of breakfast eaters and skippers. Studies showed that skipping breakfast was correlated to obesity [71,72,73]. However, the population studied was different from ours, as our study evaluated the low-income Brazilian population using the CRs as the main source of food at lunch.…”
Section: Discussionmentioning
confidence: 91%
“…The risk of bias in included studies was assessed by applying the "Risk Of Bias In Non-randomized Studies of Interventions" (ROBINS-I) tool [65] for each study (Supplementary Table S2). Along with the risk of bias due to confounding, age, sex, education or socioeconomic status, smoking, alcohol, physical activity and total energy intake (TEI) were established in accordance with the literature [31,34,40,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]; as these are important covariables because of their confounding nature of being associated with breakfast and body weight. Moreover, the quality of evidence of the conducted meta-analyses was assessed by using the "Nutrition Grading of Recommendations Assessment, Development and Evaluation" (NutriGRADE) approach [82] (Supplementary Table S3).…”
Section: Data Extraction and Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…Another study [110] reports an increased BMI with increasing economic status in both, women and men. With increasing age, the likelihood of overweight/obesity increased, too [62]. The sex gradient indicates that women are more likely to be overweight/obese, globally [112].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias in included studies was assessed by applying the "Risk Of Bias In Non-randomized Studies of Interventions" (ROBINS-I) tool [60] on each study (Supplementary Appendix, Table S2). Along with the risk of bias due to confounding, age, sex, education or socioeconomic status, smoking, alcohol, physical activity and total energy intake (TEI) were established in accordance with the literature [27,29,35,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] as important covariables because of their confounding nature of being associated with breakfast and body weight. Moreover, the quality of evidence of the conducted meta-analyses was assessed by using the "Nutrition Grading of Recommendations Assessment, Development and Evaluation" (NutriGRADE) approach [77] (Supplementary Appendix, Table S3).…”
Section: Data Extraction and Quality Assessment Of Included Studiesmentioning
confidence: 99%